Spent Mushroom Substrate-Derived Biochar and Its Applications in Modern Agricultural Systems: An Extensive Overview - Worawoot Aiduang; Kritsana Jatuwong; Tanongkiat Kiatsiriroat; Wassana Kamopas; Pimsiri Tiyayon; Rotsukon Jawana; Orlavanh Xayyavong; Saisamorn Lumyong (Life)
Spent mushroom substrate (SMS), a nutrient-dense byproduct of mushroom cultivation, has emerged as a promising feedstock for biochar production, offering a sustainable solution to modern agricultural and environmental challenges. This review explores SMS properties, its conversion into biochar, and its various applications. Due to its lignocellulosic structure, high organic matter (OM), and essential nutrients, SMS is ideal for pyrolysis, a process that enhances biochar’s porosity, nutrient retention, and carbon stability. These properties improve soil fertility, water retention, microbial activity, and plant growth while also contributing to climate change mitigation through carbon sequestration. SMS-derived biochar stands out for its superior benefits, including a balanced pH, a rich nutrient profile, and the ability to adsorb heavy metals, which mitigates soil and water contamination and minimizes toxic risks in the food chain. By enhancing soil structure, nutrient cycling, and moisture retention, SMS-derived biochar supports sustainable farming practices that reduce chemical fertilizer use and boost climate resilience. Beyond soil applications, SMS-derived biochar is effective in wastewater treatment, mitigating plant diseases, and improving mushroom cultivation substrates, thereby enhancing mycelial growth and productivity. Economically, it is a cost-effective alternative due to the abundant availability and inexpensive nature of SMS. Nevertheless, challenges still exist, particularly in optimizing production methods and ensuring consistency in biochar properties, influenced by variations in pyrolysis conditions and SMS types. Advances in production technology and sustainable practices are vital for scaling up SMS-derived biochar production. This paper emphasizes the transformative potential of SMS-derived biochar, advocating for its integration into circular economy frameworks and sustainable agricultural systems. Recommendations for future research and policy support are provided to maximize the ecological and economic benefits of SMS-derived biochar, fostering its widespread adoption in global agricultural and environmental strategies.